The Gut Microbiota and Autism Spectrum Disorders - Li, Qinrui; Han, Ying; Dy, Angel Belle C.; Hagerman, Randi J. (Frontiers in Cellular Neuroscience, 2017)
Gastrointestinal (GI) symptoms are a common comorbidity in patients with autism spectrum disorder (ASD), but the underlying mechanisms are unknown. Many studies have shown alterations in the composition of the fecal flora and metabolic products of the gut microbiome in patients with ASD. The gut microbiota influences brain development and behaviors through the neuroendocrine, neuroimmune and autonomic nervous systems. In addition, an abnormal gut microbiota is associated with several diseases, such as inflammatory bowel disease (IBD), ASD and mood disorders. Here, we review the bidirectional interactions between the central nervous system and the gastrointestinal tract (brain-gut axis) and the role of the gut microbiota in the central nervous system and ASD. Microbiome-mediated therapies might be a safe and effective treatment for ASD.